TINDAKAN PEMERINTAH DAERAH KABUPATEN BADUNG DALAM MENEGAKKAN IZIN GANGGUAN (HO) UNTUK CLUB MALAM - Wisnu Saputra, I Wayan; Sudiarta, I Ketut; Dahana, Cokorda Dalem (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
As the development of the tourism industry, there are many night clubs in Badung. Implementation night club will cause interference to the environment around the night club. Associated with the onset of interference by a business field that is set in the Badung Regency Regulation No. 9 of 2010 on the nuisance permit. the author will discuss the enforcement of nuisance permit HO (Hinder Ordinance) for the night club in Badung and factors that impede law enforcement HO permission. This paper using the methods of empirical legal research. conclusions obtained 1. Enforcement of permit interference in Badung not go according to the laws and regulations 2. Barriers Government in enforcing the Badung Regency Regulation No. 3 of 2010 concerning Permits disorders, lack of technical personnel and civil servants investigator supervisor (investigators) to conduct field supervision.
Keywords: Action,Permit Hinder Ordonantie disorders,night club